Septic arthritis complicating Streptobacillus moniliformis rat bite fever: a case report and review of its pathophysiology and diagnosis - Giraudon, Emmanuelle; Larranaga Lapique, Eva; Wallemacq, Silvio; Dalborgo, Marie; Yin, Nicolas; Hites, Maya; Martiny, Delphine (Frontiers in Medicine, 2024)
Rat bite fever is characterized by a clinical triad of symptoms, fever, rash and arthritis. It is transmitted by rodents and mainly due to infection by Streptobacillus moniliformis, a fastidious bacterium carried by Rattus norvegicus. This case report presents the case of a patient who developed septic arthritis and fever after a wild rat bite, with subsequent isolation of S. moniliformis from the joint fluid. Upon reviewing 45 other published case reports of S. moniliformis osteoarticular infections following contact with either a rat or its secretions, it was firstly observed that the rat bite fever clinical triad was incomplete in over half of the cases, mainly because rash was infrequently observed among adult patients. Secondly, the clinical presentation of rat bite fever is quite non-specific and rodent exposure is not mentioned by patients in a third of cases upon admission. Altogether, diagnosing rat bite fever is a significant clinical challenge suggesting that it might be significantly underdiagnosed. In addition to these clinical aspects, no evidence was found supporting immunological mechanisms, as suggested in some literature. Instead, when excluding five improperly performed cultures, S. moniliformis was cultured in 25 reported cases and identified twice by direct PCR sequencing amounting to a detection rate of 90% (n = 27/30) on joint fluids. Cultures should be performed in medium containing yeast extract, complete peptic digest of animal tissue and at least 5% blood. Knowing that S. moniliformis is very sensitive to many antibiotics thereby making the culture negative, direct 16S rRNA gene sequencing on joint fluid is an alternative method in the case of clinical and cytological evidence of osteoarticular infections with sterile culture of joint fluid.